Pengaruh perceived benefits, perceived risks, hedonic motivations, psychological factors dan website design terhadap online buying behavior - RININTA INDAH PEKERTI; VITA BRILIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of the research is to examine the influence of perceived benefits, perceived risks, hedonic shopping motivations, psychological factors, website designs on online buying behaviour. The research design used in descriptive research and causality research. The sampling in the study was purposive sampling and uses 100 responded. The respondents of this study were women who make online purchases through the website www.zalora.co.id. Data were analyzed using multiple regression analysis. The result showed that there is a significant influence of perceived benefits, perceived risks, hedonic shopping motivations, psychological factors, website designs on online buying behavior.